Penicillin acylases revisited: importance beyond their industrial utility - Avinash, Vellore Sunder; Pundle, Archana Vishnu; Ramasamy, Sureshkumar; Suresh, Cheravakkattu Gopalan (Critical Reviews In Biotechnology, 2016)
It is of great importance to study the physiological roles of enzymes in nature; however, in some cases, it is not easily apparent. Penicillin acylases are pharmaceutically important enzymes that cleave the acyl side chains of penicillins, thus paving the way for production of newer semi-synthetic antibiotics. They are classified according to the type of penicillin (G or V) that they preferentially hydrolyze. Penicillin acylases are also used in the resolution of racemic mixtures and peptide synthesis. However, it is rather unfortunate that the focus on the use of penicillin acylases for industrial applications has stolen the spotlight from the study of the importance of these enzymes in natural metabolism. The penicillin acylases, so far characterized from different organisms, show differences in their structural nature and substrate spectrum. These enzymes are also closely related to the bacterial signalling phenomenon, quorum sensing, as detailed in this review. This review details studies on biochemical and structural characteristics of recently discovered penicillin acylases. We also attempt to organize the available insights into the possible in vivo role of penicillin acylases and related enzymes and emphasize the need to refocus research efforts in this direction.
Keywords: beta-lactam; choloyl glycine; in vivo role; Ntn hydrolases; pathogenicity; quorum sensing; regulation; signalling

Serum responsive proteome reveals correlation between oxidative phosphorylation and morphogenesis in Candida albicans ATCC10231 - Ahmed, Radfan; Kodgire, Santosh; Santhakumari, B.; Patil, Rajendra; Kulkarni, Mahesh J.; Zore, Gajanan (Journal of Proteomics, 2018)
To understand the impact of fetal bovine serum (FBS) on metabolism and cellular architecture in addition to morphogenesis, we have identified FBS responsive proteome of Candida albicans. FBS induced 34% hyphae and 60% pseudohyphae in C. albicans at 30 C while 98% hyphae at 37 C. LC-MS/MS analysis revealed that 285 proteins modulated significantly in response to FBS at 30 degrees C and 37 degrees C. Out of which 152 were upregulated and 62 were downregulated at 30 degrees C while 18 were up and 53 were downregulated at 37 degrees C. Functional annotation suggests that FBS may inhibit glycolysis and fermentative pathway and enhance oxidative phosphorylation (OxPhos), TCA cycle, amino acid and fatty acid metabolism indicating a use of alternative energy source by C. albicans. OxPhos inhibition assay using sodium azide corroborated the correlation between inhibition of glycolysis and enhanced OxPhos with pseudohyphae formation. C. albicans induced hyphae in response to FBS irrespective of down regulation of Rasl,Asrl/Asr2, indicates the possible involvement of MAPK and cAMP-PKA independent pathway. The Cell wall of cells grown in presence of FBS at 30 degrees C was rich in mannan, Beta 1,3glucan and chitin while membranes were rich in ergosterol compared to those grown at 37 degrees C. Significance of the study: This is the first study suggesting a correlation between OxPhos and morphogenesis especially pseudohyphae formation in C. albicans. Our data also indicate that fetal bovine serum (FBS) induced morphogenesis is multifactorial and may involve MAPK and cAMP-PKA independent pathway. In addition to morphogenesis, our study provides an insight in to the modulation of metabolism and cellular architecture of C. albicans in response to FBS.
Keywords: analysis; Candida albicans; Fetal bovin serum; Liquid chromatography mass spectrometry; morphogenesis; Oxidative phosphorylation; pathogenicity

Genetic diversity of toxigenic Fusarium verticillioides associated with maize grains, India - Navale, Vishwambar D.; Sawant, Amol M.; Vamkudoth, Koteswara Rao (Genetics and Molecular Biology, 2023)
In the present investigation, prevalence, genetic diversity, and mycotoxin producing potential of Fusarium species associated with maize grain samples were studied from different geographical regions of India. The highest prevalence of Fusarium verticillioides was recorded as 88.52%, followed by F. coffeatum, F. foetens, and F. euwallaceae, 6.55%, 3.27%, and 1.63%, respectively. We isolated 54 strains of F. verticillioides, and their genetic diversity was studied by inter simple sequence repeats (ISSR). The ISSR fingerprints (AG) 8C and (AG) 8G showed 252 and 368 microsatellite sites in the genome of F. verticillioides and resulted in 99-100% repeatability and reproducibility. The Simpson (SID) and Shannon (H) indices (0.78 and 2.36) suggest that F. verticillioides strains exhibit moderate to high diversity. Molecular detection of fumonisin B1 (FB1) biosynthetic genes (FUM1 and FUM13) involved in FB1 production in F. verticillioides was confirmed by polymerase chain reaction (PCR). Furthermore, 91% of the strains were positive for FB1 production, which was affirmed by liquid chromatography with tandem mass spectrometry (LC-MS-MS). In-vitro appurtenance of F. verticillioides spores exhibited a high to moderate effect on the growth and development of the maize. The current finding demonstrated that most F. verticillioides strains showed a wide range of genetic diversity with varied toxigenic and pathogenic potentials. In conclusion, for the first time, F. coffeatum, F. foetens, and F. euwallaceae species were reported from maize grain samples in India. They were positive for FB1 and negatively affecting grain quality, which is a major concern in food safety.
Keywords: diversity; Food safety; Fusarium verticillioides; Mycotoxin; pathogenicity